The population of bacteria between compost and biochar-compost mixture at the different ratio / Nurul ‘Izzati Mohd. Rahim - Mohd. Rahim, Nurul ‘Izzati (Faculty of Plantation and Agrotechnology, 2019)
Abundance of waste from oil palm industry can be utilized as a beneficial by-product such as empty fruit bunch (EFB) and compost. Many study have conducted on the benefit of these by-product but lacking of interaction between them in-term of microbiology perspective. Therefore, this study was conducted with the first objective to observe the population number of microorganism present on the closed culture under laboratory for 3 months of incubation period. Second objective was to determine the best ratio of empty fruit bunch (EFB) compost and empty fruit bunch (EFB) biochar-compost mixture at different ratio and observe the best of period time biochar-compost mixture incubation for bacteria population. The bacterial colonies were present on closed culture in all mixture. The best biochar-compost mixture was found in ratio 1:1 (C:B). At the beginning of study, the number of bacterial colonies is higher as compared with another month.